Jim Johnson, Trumpet, Faculty Recital Series - Johnson, Jim; Arrington, Amanda; Hunt, Paul (Kansas State University; School of Music, Theatre, and Dance, 2018)
Monday, February 12th, 2018 7:30 p.m. All Faiths Chapel J.B.G. Neruda - Concerto in E-flat Major I. Allegro II. Largo III. Vivace Alan Hovhaness - Prayer of Saint Gregory Kevin McKee - Song for a Friend Joseph Turrin - Fandago